1987
DOI: 10.1139/m87-059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rifampin resistance on nodulating competitiveness of Rhizobium meliloti

Abstract: An assessment was made of the effect of high concentration rifampin resistance on the nodulating competitiveness of five strains of Rhizobium meliloti. The results indicate that the acquisition of rifampin resistance by R. meliloti is generally associated with a significant loss of nodulating competitiveness and an altered RNA polymerase insensitive to the action of rifampin. All mutants were similar to their parent strains with respect to growth rates, phage sensitivity patterns, and symbiotic effectiveness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…(2, 12, 13) and Rhizobium spp. (10,29). These studies demonstrated that chromosomally mediated rifampin resistance does not affect the colonizing ability of strain WCS358, confirming the results of Glandorf et al (19).…”
Section: Discussionsupporting
confidence: 87%
“…(2, 12, 13) and Rhizobium spp. (10,29). These studies demonstrated that chromosomally mediated rifampin resistance does not affect the colonizing ability of strain WCS358, confirming the results of Glandorf et al (19).…”
Section: Discussionsupporting
confidence: 87%
“…Selection of chromosomal-mediated antibiotic resistance often results in associated genetic changes which influence ecologically important traits (Andrews, 1986). Rifampicin resistance has been reported to diminish symbiotic effectiveness (Pankhurst, 1977) and nodulating competitiveness (Lewis et al, 1987) of Rhizobium spp. Davies and Whitbread (1989) reported an increase in the number of nonfluorescent colonies when Rift mutants of strains of fluorescent Pseudomonas were cultured in liquid KB medium in the presence of iron.…”
Section: Discussionmentioning
confidence: 99%
“…However, it cannot be excluded that rifampicin resistance can change characteristics in the Pseudomonas strains used, or is unstable under field conditions. Among Rhizobium spp., spontaneous rifampicin resistance (Rift) was associated with diminished symbiotic effectiveness and nodulating competitiveness (Lewis et al, 1987;Pankhurst, 1977). Certain Rift mutants of P. fluorescens were less able to compete with the parental strain in sterile soil (Compeau et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mutation to streptomycin and erythromycin resistance did not adversely affect the symbiotic N 2 -fixation system in these strains. Although similarity in N 2 -fixation capacity between spontaneous antibiotic-resistant mutants and (brady)rhizobia parental strains has been shown by others (Gollobin and Levin 1974;Levin and Montgomery 1974;Lewis et al 1987), this is not always the case (Bromfield and Jones 1979;Date and Hurse 1992;Pankhurst 1977;Schwinghamer and Dudman 1973;Turco et al 1986). Therefore, evaluation of symbiotic properties is essential before a mutant can be used to represent its parent in ecological studies.…”
Section: Symbiotic Efficiency Of Mutantsmentioning
confidence: 91%